Influence of the Dialysis Membrane on Markers of Tissue Ischemia. (1st March 2006) - Carrega, Louis; Giaime, Philippe; Montserrat, Colette; Vincente, Olivia; Brunet, Philippe; Dussol, Bertrand; Berland, Yvon; Guieu, Regis
Abstract : Background: Hemodialysis (HD) is often accompanied by adverse effects, such as tissue ischemia. We have already observed an increase in plasma adenosine (ADO) levels during HD sessions, which may be the result of tissue ischemia. Here we evaluate the influence of the dialysis membrane on two sensitive and early markers of ischemia: ADO and ischemia-modified albumin (IMA). Methods: We included in the study 50 patients with end-stage renal failure, 39 hemodialyzed (mean age 61 ± 24 years; 24 male; membranes: 23 synthetic and 16 cellulose based) and 11 undialyzed (mean age 55 ± 12 years; 6 male), and 10 healthy subjects (mean age 47 ± 11 years; 4 male). We compensated for hemoconcentration during HD by measuring either the IMA to albumin (Alb) or the ADO to Alb ratio. Results: Under basal conditions, the IMA to Alb ratio was not significantly different in patients and controls and HD did not significantly modify this ratio. Conversely, the ADO to Alb ratio (mean ± SD in μmol/g) was higher in patients before HD compared with either undialyzed patients or controls (before HD: 0.077 ± 0.02; undialyzed patients: 0.026 ± 0.11; controls: 0.022 ± 0.01). During HD, there was a significant increase in the ADO to Alb ratio (before HD: 0.077 ± 0.02; after HD: 0.09 ± 0.029; p < .01). We found no significant difference in the IMA to Alb or ADO to Alb ratio using either synthetic or cellulose-based membranes. Conclusions: We concluded that ADO is a more sensitive marker of ischemia than IMA and that, under our HD conditions, the ischemia caused by HD was very weak, independent of the dialysis membrane.